Enhanced - Innuendo; Positive Tone.; EMI (Malaysia). (Petaling Jaya, Selangor : Positive Tone, 1998)
Terdapat sepuluh buah lagu remix dalam album ini. Album ini juga memuatkan ciri Enhanced CD yang mengandungi biografi ahli kumpulan Innuendo serta bonus video untuk lagu Just For You dan Belaian Jiwa.
CD 1 : Tell Me (Funkin' Remix) / (5:54) -- Belaian Jiwa / (4:32) -- If I Could ('endo Feel) / (5:20) -- The Way We Like It (Chaos Mix) / (4:56) -- Come On With Me (Chaos Mix) / (5:39) -- Don't You Wanna Be (Wanna Get My Groove On Mix) / (4:50) -- Booties In The City (Chaos Mix) / (4:04) -- Selamanya (Acoustic Jam Mix) / (4:40) -- Just For You (Bumpin' Good Remix) / (5:07) -- If I Could (Rev/Ffwd Mix #2) / (5:26).
Koleksi Khas Wiramanja.
This Enhanced CD is for use in CD players and multimedia computers. System requirements for Bonus Videos: MACINTOSH: System 7.1 or later/68040 Processor or better, 8 MB RAM, 3 MB Free Space on Hard Driver, 14' color monitor (256 colors), CD-ROM Drive (4x speed or better), Quicktime 2.1 (included). WINDOWS: Windows 95 or later / Pentium Processor or better, MPC compatible 8 MB RAM, 3 MB Free Space on Hard Driver, 14' SVGA Monitor plus graphics card to support 640x480 @ 256 colors, CD-ROM Drive (4x speed or beter), Quicktime 2.1 (included).
Title from disc label.
Keywords: Songs, Malay; Songs, English -- Malaysia